Investigating Acceptance of Electronics Medical Record: Applying TAM Model - Rochmah, Irma Nuur; Zakiyah, Erna; Kurnianingsih, Widya; Purnomo, Bambang Eka (Procedia of Engineering and Life Science, 2024)
Electronic medical records are used to increase interoperability, efficiency and flexibility in medical record services. There are many obstacles in implementing electronic medical records at Clinic ‘X’ Sukoharjo, but this does not prevent health workers from using them. Investigation of users of electronic medical records needs to be carried out to determine the perceptions of health workers. TAM is a model that we use to determine user acceptance of technology. The TAM variables used are Perceived ease of use (PEU), Perceived Usefulness (PU), Attitude towards Using (IU), and Actual Usage (AU). The sample we used was 30 health workers. Our data was collected and calculated using PLS-SEM with the SmartPLS 4 application. The results of this research show that health workers feel helped by the existence of electronic medical records. The ease of using technology helps health workers in their work. So electronic medical records are considered useful for health workers. This usefulness encourages health workers' behavioral interest in using electronic medical records to improve their performance.